Positive Psychotherapy's Theory of the Capacity to Know as Explication of Unconscious Contents - Cope, Theo A. (Journal of religion and health, 2009)
Positive Psychotherapy (PPT), founded by Dr. Nossrat Peseschkian, a Persian Bahá'í who has lived in Europe for many years, assumes the functional capacities of the unconscious to be basic capacities.' PPT makes a distinction between actual capacities and basic capacities. The basic capacities are the capacity to love and the capacity to know. These basic capacities are comprehensive categories underpinning primary and secondary capacities. Based upon Bahá'í teachings, this therapy accepts belief as an implicit aspect of healthy psychological functioning. Moreover, contents of the unconscious in PPT are the conflicts between capacities, and undifferentiated and undeveloped actual capacities.